Development of kenaf fibre poly (lactic acid) - epoxidised jatropha oil biocomposites - Kamarudin, Siti Hasnah (2018)
Poly (lactic acid) (PLA) has been highlighted to be a useful material in substituting the petroleum based polymer due to its promising mechanical properties and biodegradability. However, its brittleness properties and higher price as compared with the common commodity plastics have limited its application. Thus, the addition of epoxidised jatropha oil (EJO), a type of biodegradable plasticiser from natural products was employed to the PLA in response to concern about the environment as well as modifying the brittleness of PLA. Kenaf, one source of environmentally friendly and abundantly cheap natural fibers has been used in this study as reinforcement in PLA. Despite the advantages of using kenaf as a natural fibre, their limitations include, poor moisture resistance, poor wettability by the hydrophobic matrix and insufficient adhesion between fibre and polymeric matrix which can lead to poor properties. Therefore, one way to improve the fibre/matrix interfacial bonding is through the incorporation of fibre surface modification or treatment. The aim of this study is to investigate the effect of EJO as plasticiser on mechanical, physical, thermal and morphology properties of PLA. Furthermore, the effect of NaOH treatment on the properties of PLA/Kenaf composites as well as PLA/Kenaf/EJO composites were studied. Five different weight percentages of EJO ranging from 1 wt.% to 5 9 were melt blended in the Brabender internal mixer prior to compression moulding of blend in a hot press and compared to a neat PLA matrix sample. The mechanical properties of PLA/EJO composites were characterised in terms of tensile strength, tensile modulus, flexural strength, flexural modulus and impact strength. Results showed that the tensile strength, tensile modulus, flexural strength and flexural modulus decreased with increasing content of EJO in the blend. On the other hand, with the further addition of EJO to the PLA composites, the elongation at break properties increased significantly by 8.1% to 78.4%. The FTIR study indicated that miscibility and interaction of PLA and EJO exist as a small shift towards a higher temperature appeared in the absorption peak of PLA/EJO blend. Moreover, the study findings showed that the water absorption of plasticized PLA decreased significantly by 1.3% to 1.0% with increasing EJO concentration up to 5 wt.%. While for thermal properties, the Differential Scanning Calorimetry (DSC) measurement revealed that the addition of EJO resulted in a decrease of glass transition temperature up to 62.2°C which aids PLA chain mobility in the blend as predicted. In addition, the Thermogravimetric Analysis (TGA) showed that the presence of EJO in the blends reduce the rate of decomposition of PLA by increment of onset temperature up to 388.2°C and enhanced the thermal stability of the blend. The improvement in mechanical, physical and thermal properties of PLA/EJO composites indicating better polymer-plasticiser interaction which is proved by Scanning Electron Micrograph (SEM) analysis. Afterward, five different weight percentages of kenaf fibre loading ranging from 10 wt.% to 50 wt.% were employed in the PLA blends in order to study the optimum fibre loading value in the blend. As a result, 40 wt.% of kenaf fibre loading found to be the optimum value for PLA/kenaf biocomposites. The surface modification treatment with 6% NaOH on kenaf fibre enhanced the properties of biocomposites as compared to the untreated kenaf fibre. The incorporation of EJO as a plasticiser to modify the brittleness of PLA demonstrated that the plasticised PLA/Kenaf bicomposites with good mechanical and thermal properties could be developed. It can be concluded that the addition of plasticiser and the treatment of fibre improved the properties of PLA/Kenaf/EJO biocomposites. Out of the analyses subjected, PLA (57 wt/%) / Kenaf (40 wt.%) /EJO (3 wt.%) reported as the best formulation of biocomposite from this study. Hence, the study findings will pave the way towards a greater usage of vegetable oil as well as natural fibre for the commercialisation and mankind benefits which can replace petroleum-derived products in the long run. Specific applications for the studied materials involved interior parts of the car, environmental packaging, tray and box.